PERENCANAAN SISTEM PENYEDIAAN AIR BERSIH PDAM KOTA SALATIGA - Arif Kurniawan; Agus Priyanto; Suripin Suripin; Salamun Salamun (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
PDAM water supply services Salatiga still faced with various technical, financial and institutional problems. To overcome these problems we need a strategy of how to remedy the problems based on technical, financial and institutional aspects. With these strategies, it’s expected, the water services to the community can be improved, in order to get access and reduction of water loss up to 25% can be achieved the target of 85% services. Evaluation results so that the availability of the technical aspects of water sources Salatiga urban areas do not meet the minimum water needs up to 10 years, coverage is still low,the leakage rate is still high and the condition of the existing transmission and distribution pipelines still need to be addressed .While a better performance of PDAM Salatiga needs take a few strategies releted to finance and management techniques.